A Survey of Secure Internet of Things in Relation to Blockchain - Alizadeh, Morteza; Andersson, Karl; Schelén, Olov (Luleå tekniska universitet, Datavetenskap, 2020)
Distributed ledgers and blockchain technologies can improve system security and trustworthiness by providing immutable replicated histories of data. Blockchain is a linked list of blocks containing digitally signed transactions, a cryptographic hash of the previous block, and a timestamp stored in a decentralized and distributed network. The Internet of Things (IoT) is one of the application domains in which security based on blockchain is discussed. In this article, we review the structure and architectures of distributed IoT systems and explain the motivations, challenges, and needs of blockchain to secure such systems. However, there are substantial threats and attacks to blockchain that must be understood, as well as suitable approaches to mitigate them. We, therefore, survey the most common attacks to blockchain systems and the solutions to mitigate them, with the objective of assessing how malicious these attacks are in the IoT context. Validerad;2020;Nivå 1;2020-09-14 (alebob) DIT4BEARS: Disruptive IT for Barents Euro-Arctic Regions Blockchains for raw materials traceability: Dynamic identities in refinement-based value chains